Evaluation of relationship between Chilean octopus (Octopus mimus Gould, 1852) egg health condition and the egg bacterial community. (7th July 2014) - Iehata, Shunpei; Valenzuela, Fernando; Riquelme, Carlos
Abstract: The objective of this study was to evaluate how bacterial community associated with Chilean octopus ( Octopus mimus ) egg was related to egg health condition using a culture dependent method and PCR‐DGGE fingerprinting technique. Total heterotrophic bacterial number of fresh egg was much lower than infected egg. However, biodiversity of culturable bacterial community associated with the fresh egg exhibited a higher diversity than the infected egg. Result of a culture dependent method showed that Roseobacter clade was predominant in the fresh egg, while predominant species in the infected egg was γ‐proteobacteria. DGGE fingerprinting technique showed that fresh egg associated unculturable bacterial community was constituted of Roseobacter clade and Bacteroidetes, whereas Bacteroidetes was predominant bacteria in the infected egg. These results suggest that there might be some sort of relationship between octopus eggs associated bacterial community and egg health condition. Moreover, Roseobacter clade and Bacteroidetes might be potential symbiotic bacteria associated with the octopus egg, and some γ‐proteobacteria might be involved in octopus egg disease. In particular, Roseobacter clade may play an important role in octopus egg health and it raises the possibility that this clade can be utilized as potential probiotics for octopus aquaculture.